Analysis Of Improving The Layout Of Warehouse Accessories Facilities In PT Delapan Jaya Perkasa Garment - Rahmatul Ahya; Amir Amir (International Journal of Economics and Management Research, 2024)
PT Empat Jaya Perkasa Garmen is a company located in Bendungan, Kebayanan Jetis, Pilangsari, Kec. Ngrampal, Sragen Regency, Central Java 57252, operates in the garment industry and its production system is based on make to order. High consumer demand causes the production process to increase. This also affects warehouse management activities. Storage conditions and arrangement of goods that are carried out randomly and irregularly will result in the accumulation of goods or mixing of goods in one rack slot. So, this condition will result in a longer search time. This study discusses improving warehouse layout and arranging goods using the Class Based Storage method for process-focused manufacturing or service facilities. The research was carried out by examining products in the accessories warehouse with the aim of finding out the layout of goods in the accessories warehouse, to fulfill the need for searching for goods accurately by looking for the causes of irregular placement and arrangement of goods, then creating a layout of goods in the accessories warehouse. The arrangement of goods is carried out based on the type of goods by means of one rack slot being used for one type of goods. So that the material handling process runs smoothly.